Correlation of SIN3A genomic variants with β-hemoglobinopathies disease severity and hydroxyurea treatment efficacy. (November 2016) - Gravia, Aikaterini; Chondrou, Vasiliki; Kolliopoulou, Alexandra; Kourakli, Alexandra; John, Anne; Symeonidis, Argyris; Ali, Bassam R; Sgourou, Argyro; Papachatzopoulou, Adamantia; Katsila, Theodora; Patrinos, George P
Aims: Hemoglobinopathies, particularly β-thalassemia and sickle cell disease, are characterized by great phenotypic variability in terms of disease severity, while notable differences have been observed in hydroxyurea treatment efficacy. In both cases, the observed phenotypic diversity is mostly dependent on the elevated fetal hemoglobin levels, resulting from the persistent fetal globin gene expression in the adult erythroid stage orchestrated by intricate mechanisms that still remain only partly understood. We have previously shown that several protein factors act as modifiers of fetal hemoglobin production, exerting their effect via different pathways.Materials & methods: Here, we explored whether SIN3A could act as a modifier of fetal globin gene expression, as it interacts with KLF10, a known modifier of fetal hemoglobin production.Results: We show that SIN3A genomic variants are associated both with β-thalassemia disease severity (rs11072544) as well as hydroxyurea treatment response (rs7166737) in β-hemoglobinopathies patients.Conclusion: Our findings further underline that fetal hemoglobin production is the result of a complex interplay in which several human globin gene cluster variants interact with protein factors encoded by modifier genes to produce the observed clinical outcome.